2019
DOI: 10.29011/2688-6383.000046
|View full text |Cite
|
Sign up to set email alerts
|

Instructions on how to make an Outbreak of American Cutaneous Leishmaniasis

Abstract: Outbreaks of American Cutaneous Leishmaniasis (ACL) are triggered by the confluence of multidimensional biological, climate, and social factors: the eco-epidemiological momentum. Despite the diversity of epidemiological scenarios, there are common "Ingredients for the recipe" to make an ACL outbreak. To describe the "Where", "When", and "Why" of this momentum could contribute to the understanding of the causes of epidemics, preventing their occurrence, and to define better strategies to control them. Typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 193 publications
0
3
0
Order By: Relevance
“…However, although the sites where the vector and cases were recorded coincide, it is not possible to state that the site of the reporting is the same as the transmission site, as only the residence or place of diagnosis is the usually recorded data. Meanwhile, the place of transmission may be even in localities far away of the residence related to recreational or work activities within areas of wild vegetation (e.g., fishing, hunting, or forest clearing work), where the vectors involved in transmission are generally found (Salomón, 2019). In order to evaluate the possible sites of transmission and predict the appearance of new cases, it is important to record and detect new vector-competent species in time, for which vector surveillance and knowledge of the species present are essential.…”
Section: New Records For Corrientes Provincementioning
confidence: 99%
“…However, although the sites where the vector and cases were recorded coincide, it is not possible to state that the site of the reporting is the same as the transmission site, as only the residence or place of diagnosis is the usually recorded data. Meanwhile, the place of transmission may be even in localities far away of the residence related to recreational or work activities within areas of wild vegetation (e.g., fishing, hunting, or forest clearing work), where the vectors involved in transmission are generally found (Salomón, 2019). In order to evaluate the possible sites of transmission and predict the appearance of new cases, it is important to record and detect new vector-competent species in time, for which vector surveillance and knowledge of the species present are essential.…”
Section: New Records For Corrientes Provincementioning
confidence: 99%
“…In Argentina, Misiones province is endemic for this disease, with more than 2900 confirmed cases since 2006 (National Health Ministry, 2020). Outbreak studies demonstrated patterns of infection cycles in peri‐urban areas close to primary or residual forest, in rural areas or urban–rural interfaces (Andreo et al., 2022; Salomon, 2019; Salomón et al., 2001, 2006). Nevertheless, there exists an epidemiological pattern of transmission associated with more intensive exposure to vector contact in sylvatic areas.…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by trypanosomatid parasites of the genus Leishmania, which are transmitted by dipterans of the Phlebotominae subfamily (Killick-Kendrick, 1990).In South America, one of the various agents of ACL, Leishmania (Viannia) braziliensis, is associated with an ulcerative and stigmatizing mucocutaneous pathology (PAHO, 2019). In Argentina, Misiones province is endemic for this disease, with more than 2900 confirmed cases since 2006 (National Health Ministry, 2020).Outbreak studies demonstrated patterns of infection cycles in peri-urban areas close to primary or residual forest, in rural areas or urban-rural interfaces (Andreo et al, 2022;Salomon, 2019;Salomón et al, 2001Salomón et al, , 2006. Nevertheless, there exists an epidemiological pattern of transmission associated with more intensive exposure to vector contact in sylvatic areas.…”
mentioning
confidence: 99%